A Flexible Ionic Liquid Gelled PVA‐Li2SO4 Polymer Electrolyte for Semi‐Solid‐State Supercapacitors. Issue 15 (13th August 2015) - Zhang, Xing; Wang, Liangliang; Peng, Jing; Cao, Pengfei; Cai, Xiaosheng; Li, Jiuqiang; Zhai, Maolin
<x xml:space="preserve">Abstract</x> A novel high‐performance flexible gel polymer electrolyte (FGPE) for supercapacitors is prepared by a freeze‐drying method. In the presence of 1‐butyl‐3‐methylimidazolium chloride (BMIMCl) ionic liquid, Li2SO4 can easily be added into poly(vinyl alcohol) (PVA) aqueous solution over a large concentration range. The resultant FGPE demonstrates considerably high ionic conductivity (37 mS cm−1) and a high fracture strain at 100% elongation at the optimal weight ratio of PVA:BMIMCl:Li2SO4 = 1:3:2.2. The supercapacitor fabricated with the resultant FGPE and activated carbon electrodes shows an electrode‐specific capacitance of 136 F g−1 with a stable operating voltage of 1.5 V, a maximum energy density of 10.6 Wh kg−1, and a power density of 3400 W kg−1. Double supercapacitors in series can efficiently drive a light emitting diode (LED) bulb for over 5 min and the retention of the specific capacitance reaches 90% even after 3000 charge–discharge cycles. The ionic conductivity and charge–discharge behaviors of the resultant FGPE are not affected by bending up to 180°. The flexible supercapacitor device shows only a small capacitance loss of 18% after 1000 cycles of 135° bending.